Responding to the cholera pandemic in Budiriro Township: Implications for disaster management practices - Mahuntse, Samuel Lisenga (Midlands State University, 2021)
The cholera pandemic has become endemic in Zimbabwe and social work research in this area remains limited. Available research highlights that cholera response has been more medical and remedial in approach hence the social issues remain largely unattended to which creates an urgent need for wider research in this area for better disaster management. Against this backdrop, the goal of the study was to explore the response to the 2018 cholera pandemic in Budiriro, a township in Harare, and its implications for disaster management within the Zimbabwean context. A case study research design as the research’s guiding design. Data was collected from a sample of 25 participants and 4 key informants who were selected using purposive sampling. In-depth interviewing was used to collect data from the participants and semi-structured interview schedules were used as data collection instruments. Thematic analysis was used to analyse data. It was evident from the findings of the study that the strategies used to respond to cholera were largely effective but lacked a preventative focus. The findings also pointed to a number of challenges faced by stakeholders during the response which then compromised the efficacy of strategies used to combat cholera. The researcher then made recommendations in line with the study questions and among the recommendations, it was noted that this study will contribute to a general understanding of cholera response strategies and its efficacy. In addition, the study findings may help expose the challenges associated with cholera response and that the insights gleaned from this study may be used to inform policy, practice in settings where social workers practice disaster response and management as well as inform areas of future research.